Pengaruh Penggunaan Teknologi Informasi Sistem Informasi Manajemen Daerah (Simda) Pendapatan Terhadap Nilai Informasi Laporan Keuangan Pemerintah Kota Gorontalo - Mattoasi Mattoasi; Didiet Pratama Musue; Winra Gita Abas (Jurnal Ilmiah Akuntansi Keuangan dan Bisnis (JIKABI), 2023)
This study aims to see the influence of information technology based on regional management information system (SIMDA) revenue on the value of financial reporting information of the Gorontalo City Government. In answering the research hypothesis, quantitative research methods are used through distributing questionnaires to 58 respondents (employees) at the regional finance agency of Gorontalo  City. The data obtained were analyzed using SPSS 22 for windows.ased on the research results, it shows that the use of information technology (SIMDA)  income affects the value of financial reporting information of the Gorontalo City Government by 57.3%, while the remaining 42.7% is explained by other variables not examined in this study.